SAT0481 Setting the standard for longitudinal follow-up of systemic sclerosis; a eustar delphi-based expert consensus. (12th June 2018) - Hoffmann-Vold, A.-M.; Distler, O.; Baron, M.; Kowal-Bielecka, O.; Khanna, D.; Allanore, Y.; ,
Abstract : Background: Systemic sclerosis (SSc) is a severe multi-organ disease associated with substantial morbidity and mortality. Lung and heart involvement are currently the major causes of disease-related deaths. Skin, gastrointestinal and musculoskeletal involvement, digital ulcers and Raynaud's phenomenon have shown to be associated with high morbidity, reduced quality of life and lower social functioning. SSc is progressive and many of the disease features aggravate over time, while other features may commence during the disease course. However, to date, there are no established standardised international guidelines for follow-up of SSc patients. Objectives: The aim was to establish an expert consensus regarding the longitudinal systemic assessment of organ involvement in SSc to improve the standard-of-care for SSc patients. Methods: All experts in SSc from the European Scleroderma Trials and Research Group (EUSTAR) network and the scleroderma clinical trial consortium (SCTC) were invited to participate. The final expert panel consisted of a multidisciplinary team including rheumatologists, dermatologists, pulmonologists, cardiologists and nephrologists. The Delphi method was Internet based and completed from December 2016 until October 2017. The method entailed the entire group of experts who anonymously replied to in total 5 online questionnaires. The experts were asked to score each item in the survey to answer the following question: "Which domains and tools do you strongly suggest for the minimum annual systemic investigation of SSc patients". Every item in every questionnaire was asked to be rated between 0% and 100%, with 100% as 'very important/appropriate' and 0% as 'not important/appropriate at all'. Parameters rated >80% by more than 80% of the experts were rated as acceptable in all steps. Results: Of the 269 invited centres, physicians from 132 (49.1%) centres participated in the DELPHI survey of 5 steps. Of the included participants, 71.3% were seeing >50 SSc patients annually and 48.3% of the centres seeing >100 patients on an annual basis. Of all, 98 of the centres were located in Europe (74.2%), 18 in North America (13.6%), 7 in Asia (5.3%), 5 in South America (3.8%) and 4 in Oceania (3.0%). In the first round, 23 domains were suggested by the expert panel. After the second Delphi step, 10 domains were included (figure 1). In the third round, tools for each domain were received. The tools were included in the fourth step and rated by all participating experts. The tools for each of the 10 domains that were rated appropriately by all experts were included in the last step of the DELPHI survey and were re-rated. The final tools for each domain are shown in figure 1 and can be seen as the collective opinions of the convened expert panel. Conclusions: Through five Delphi rounds with world leading experts in SSc, an expert consensus was established on strongly suggested tools for a minimum longitudinal systemic assessment of organ involvement in SSc to improve the standard-of-care for patients with SSc. Disclosure of Interest: None declared